KOMUNITAS SEBAGAI INFRASTRUKTUR PERKEMBANGAN SENI GRAFIS DI YOGYAKARTA - Mahendrapati, Alexander Nawangseto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2018)
ABSTRACTThe research was conducted on the basis of there are at least three reasons why the first is,  there has been no mapping to the printmaking community in Yogyakarta and their activity. Second, raise awareness college students to forming a community as a receptacle for learning, working, and do the movement of together in independent to develop printmaking. Third, the results of the study to  determine  the  learning methods  that  continued  as  an  effort  to  increasing  the  quality  of  the artworks of  the students are, created  the atmosphere at work,  to providing  the socialization about printmaking  to  the  people.  Qualitative  descriptive  study  is  used  in  analyzing  the  results  of observations  are  done  continuously  thus  obtaining  a  complete  mapping  concerning  the phenomenon of the growth of the printmaking communities following the influence of existence of them  in  the  development  of  printmaking  in  Yogyakarta,  and  positive  values  to  be  adopted  or developed further as learning materials for graphic art students the Indonesia Institute of The Arts  Surakarta. The result of research conducted in the form of mapping the art community graphic in yogyakarta and recommendations on one method learning with a system of the formation of groups small  in  the  class  in  the process of  the achievement  of  the  creation  for  students, and a growing spirit to introduce printmaking to the people of Surakarta to become a branches of art popular.  Keywords: mapping , community , printmaking, popular.